KETERKAITAN KINERJA KEUANGAN DENGAN HARGA SAHAM: STUDI PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BEI - Tri Puji Rahayu; Beni Suhendra Winarso (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2021)
This study aims to investigate the effect of profitability ratios, liquidity ratios, activity ratios and leverage ratios on the stock prices of agricultural sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling technique in this study is the purposive sampling method. The type of data is quantitative research. The data sources used in the study are secondary data from the IDX website and the official website of related companies. The results show that the return on investment, earnings per share, quick ratio, and total assets turnover positively affect stock prices, while the return on equity, return on assets, current ratio, and debt ratio have a negative effect on stock prices.